Lipid and glucose metabolism in senescence - Liu, Bin; Meng, Qingfei; Gao, Xin; Sun, Huihui; Xu, Zhixiang; Wang, Yishu; Zhou, Honglan (Frontiers in Nutrition, 2023)
Senescence is an inevitable biological process. Disturbances in glucose and lipid metabolism are essential features of cellular senescence. Given the important roles of these types of metabolism, we review the evidence for how key metabolic enzymes influence senescence and how senescence-related secretory phenotypes, autophagy, apoptosis, insulin signaling pathways, and environmental factors modulate glucose and lipid homeostasis. We also discuss the metabolic alterations in abnormal senescence diseases and anti-cancer therapies that target senescence through metabolic interventions. Our work offers insights for developing pharmacological strategies to combat senescence and cancer.